2020
DOI: 10.3390/ijms21113839
|View full text |Cite
|
Sign up to set email alerts
|

miR-129-5p and miR-130a-3p Regulate VEGFR-2 Expression in Sensory and Motor Neurons during Development

Abstract: The wide-ranging influence of vascular endothelial growth factor (VEGF) within the central (CNS) and peripheral nervous system (PNS), for example through effects on axonal growth or neuronal cell survival, is mainly mediated by VEGF receptor 2 (VEGFR-2). However, the regulation of VEGFR-2 expression during development is not yet well understood. As microRNAs are considered to be key players during neuronal maturation and regenerative processes, we identified the two microRNAs (miRNAs)—miR-129-5p and miR-130a-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 69 publications
(104 reference statements)
0
10
0
Order By: Relevance
“…To identify the potential miRNA targets of HAGLR, we analyzed the HAGLR–miRNA interaction through the non-coding RNA database, starBase2.0. We observed miR-130a-3p, which plays an important role during neuron development and neuronal diseases [ 21 ], contains HAGLR binding sites ( Figure 2a ). We then evaluated the functional roles of miR-130a-3p during RA-induced neuron differentiation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To identify the potential miRNA targets of HAGLR, we analyzed the HAGLR–miRNA interaction through the non-coding RNA database, starBase2.0. We observed miR-130a-3p, which plays an important role during neuron development and neuronal diseases [ 21 ], contains HAGLR binding sites ( Figure 2a ). We then evaluated the functional roles of miR-130a-3p during RA-induced neuron differentiation.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the lncRNA–miRNA interaction has been shown to control vital functions during the molecular and cellular processes of human malignancies, including neuronal diseases [ 8 , 9 ]. A recent study reported that miR-130a-3p regulates VEGFR-2 expression in sensory and motor neurons during development [ 22 ]. Moreover, the miR-130a-3p/DAPK1 axis was known to regulate the pathophysiology of neonatal hypoxic-ischemia encephalopathy [ 23 ], suggesting miR-130-3p to be a potential therapeutic target for the hypoxic ischemia encephalopathy treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have hitherto revealed that miRNAs function by binding to a specific sequence at the 3 UTR of their target mRNAs to induce degradation and translational repression of mRNAs (O'Brien et al, 2018). A previous study showed that in sensory dorsal root ganglia, VEGFR-2 expression increased during maturation and was accompanied by an overexpression of miR-130a-3p, which indicates that miR-130a-3p may affect neuron outgrowth through VEGFR-2 (Glaesel et al, 2020). However, VEGFR-2 was not significantly changed in the selected mRNA datasets of stroke brain tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Recent literature has shown the potential roles of miRNAs, a type of small noncoding RNA in PF ( Dutta et al, 2019 ; Boateng and Krauss-Etschmann, 2020 ; Cho et al, 2020 ), which can regulate target genes or proteins through inflammatory responses related to mRNA degradation or translation inhibition. Among these miRNAs, miR-130a-3p observed in MSCs has been reported to have antitumor effects and has been used for treating neurological diseases ( Chen et al, 2010 ; Glaesel et al, 2020 ; Zhong et al, 2020 ). It has also been found that miR-130a-3p could exert cardioprotective effects through the induction of angiogenesis in ischemic hearts after myocardial infarction ( Moghaddam, et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%